2020
DOI: 10.1109/access.2020.3010050
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for the Prediction of Lead Times in an Engineer to Order Environment—A Systematic Review

Abstract: The interest of manufacturing companies in a sufficient prediction of lead times is continuously increasing -especially in engineer to order environments with typically a large number of individual parts and complex production processes. A multitude of approaches have been proposed in the literature for predicting lead times considering different data and methods or algorithms from operations research (OR) and machine learning (ML). In order to provide guidance at setting up prediction models and developing ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 74 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…ANN and RF have already proven successful in including material data in the prediction model. When looking at the data origin, the authors of [24] also identified that the use of real data strongly decreases with an increasing number of considered data classes. Thus, with increasing complexity of the prediction model they identified a lack of models using real data.…”
Section: State Of the Artmentioning
confidence: 99%
See 4 more Smart Citations
“…ANN and RF have already proven successful in including material data in the prediction model. When looking at the data origin, the authors of [24] also identified that the use of real data strongly decreases with an increasing number of considered data classes. Thus, with increasing complexity of the prediction model they identified a lack of models using real data.…”
Section: State Of the Artmentioning
confidence: 99%
“…A systematic literature review conducted by BURGGRÄF ET AL. [24] has analyzed existing approaches focusing on the prediction of lead times in the research fields of ML and OR and classified them according to the three criteria data class, data origin and used method/algorithm. Looking at the data class, the authors identified that the majority of publications examined use order data and information about the system status of the production system (see, for example, [25,26]).…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations